The utility of miR-16, miR-146a and miR-155 in serum and urine for juvenile idiopathic arthritis diagnostics and monitoring - Ausra Snipaitiene; Kristina Snipaitiene; Andzelika Slegeryte; Benita Buragaite-Staponkiene; Asta Baranauskaite; Sonata Jarmalaite; Lina Jankauskaite (Pediatric Rheumatology Online Journal)
Abstract Background Biomarker search for juvenile idiopathic arthritis (JIA) diagnosis and monitoring remain the focus of research worldwide. Several microRNAs (miRNAs) have been identified as relevant in different rheumatic conditions; however, studies in JIA remain limited. Our study aimed to explore the potential of serum and urine-derived miRNAs for JIA diagnostics and longitudinal JIA monitoring. Methods In this single-center, prospective study, three selected miRNAs (miR-16, -146a and -155) were tested in serial serum and urine samples collected from 31 JIA patients and 22 healthy controls (HC) via quantitative reverse transcription polymerase chain reaction (RT‒qPCR). The diagnostic performance of variables for distinguishing JIA patients from HCs was assessed by determining the area under the receiver operating characteristic (ROC) curve (AUC). The prediction of remission was evaluated using Cox regression and Kaplan-Meier analyses. A p-value < 0.05 was considered statistically significant. Results Lower miR-16 and higher miR-155 levels were detected in serum of JIA patients’ vs. HC (p < 0.01), whereas the level of miR-146a was lower in urine of JIA patients (p = 0.032). In ROC analysis, miR-16 and miR-155 distinguished JIA patients from HC when analyzed in serum (AUC 0.81, 95% CI 0.70–0.93, p < 0.001 and AUC 0.73, 95% CI 0.59–0.87, p = 0.005, respectively), and miR-146a– in urine (AUC 0.68, 95% CI 0.53–0.82, p = 0.030). During 12 months follow-up period increasing miR-16 (p = 0.021) and decreasing miR-155 (p = 0.009) levels were observed in serum samples. Kaplan-Meier survival analysis revealed that a high level of miR-146a in serum significantly predicts JIA remission (HR = 2.2, 95% CI 0.7–6.9, p = 0.040). Conclusions This study highlights the utility of miRNAs in JIA diagnosis, monitoring and prognosis and demonstrates the feasibility of using urine as a noninvasive source of miRNAs in children with non-systemic JIA.